2014
DOI: 10.3892/or.2014.3484
|View full text |Cite
|
Sign up to set email alerts
|

Expression and roles of fatty acid synthase in hepatocellular carcinoma

Abstract: Cell metabolism abnormalities are closely related to tumor occurrence and development. Fatty acid synthase (FASN) is the key molecule for catalyzing fatty acid synthesis. Increasing evidence indicates that FASN is highly expressed in a number of malignant tumors; it can promote the synthesis of endogenous fatty acids in tumor cells and then the synthesized fatty acids provide energy for the proliferation of tumor cells. However, there has been no systematic study focusing on FASN expression and function in hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 18 publications
2
53
1
Order By: Relevance
“…[31][32][33] In accordance with previous data, we have found a progressive upregulation of FASN mRNA from human normal livers to HCC in our sample collection (Fig. 3A).…”
Section: Increased Lipogenesis In Hccsupporting
confidence: 79%
See 1 more Smart Citation
“…[31][32][33] In accordance with previous data, we have found a progressive upregulation of FASN mRNA from human normal livers to HCC in our sample collection (Fig. 3A).…”
Section: Increased Lipogenesis In Hccsupporting
confidence: 79%
“…31,33,36 Specifically, silencing of FASN using siRNA or inhibition of FASN activity via the small molecule C75 led to decreased HCC cell proliferation and increased apoptosis. Mechanistically, it has been suggested that FASN may regulate the AKT 33 and p38MAPK 36 cascades.…”
Section: Increased Lipogenesis In Hccmentioning
confidence: 99%
“…Also, levels of FASN and other lipogenic proteins as well as polymorphisms in lipogenic genes are associated with poor outcome in HCC patients [812]. In addition, FASN suppression has been shown to be detrimental for HCC growth in vitro [10,13,14]. Despite this body of evidence, key questions about FASN in HCC remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…These tests rely primarily on structural-anatomic assessments as the basis of disease detection. With the emergence of precision medicine, it may also be useful to image liver tumors on the basis of molecular or metabolic traits, particularly if those traits can provide information on prognosis or treatment vulnerability [57]. …”
Section: Introductionmentioning
confidence: 99%